The Effect of Student-Centered Learning using the Make a Match Model on Students’ Knowledge in the Nursing Management and Patient Safety Course Among Second-Year Undergraduate Program - Yunita Fiti Rejeki; Adinda Triani Nur Hasanah; Annisa Nur Erawan (STIKep PPNI Jawa Barat, 2026)
Background: Active learning strategies are essential to improve nursing students’ understanding of Nursing Management and Patient Safety, which are critical for preventing adverse events in clinical practice. Student Centered Learning (SCL) using the Make a Match model is an interactive cooperative learning approach that promotes active engagement and conceptual understanding. However, evidence regarding its effectiveness in improving nursing students’ knowledge remains limited. Objective: This study aimed to determine the effect of Student Centered Learning using the Make a Match model on students’ knowledge in the Nursing Management and Patient Safety course among second-year undergraduate nursing students. Methods: A pre-experimental one-group pretest–posttest design was conducted involving 69 second-year undergraduate nursing students at STIKes Dharma Husada, selected through purposive sampling. Students’ knowledge was assessed using a 34-item patient safety knowledge questionnaire developed by Dhewa (2017). All enrolled participants completed both the pretest and posttest. Data normality of the pre–post difference scores was confirmed, justifying the use of a paired t-test. Statistical analysis was performed at a 0.05 significance level. Effect size was calculated using Cohen’s d, and 95% confidence intervals were estimated. Results: Prior to the intervention, most students demonstrated a moderate level of knowledge (63.8%). After the implementation of the Make a Match learning model, the majority of students achieved a good level of knowledge (91.3%). The paired t-test showed a statistically significant increase in knowledge following the intervention (p = 0.001), with a large effect size and a 95% confidence interval indicating a meaningful educational impact. Conclusion: Student Centered Learning using the Make a Match model is effective in significantly improving nursing students’ knowledge in the Nursing Management and Patient Safety course. This approach may be considered as an alternative instructional strategy to enhance learning outcomes in nursing education.